The puzzle of postpartum psychosis – nosologic position, risk factors, prognosis - Karakuła, Hanna; Pitucha, Alina; Łukasik, Paulina; Juchnowicz, Dariusz; Lecyk, Anna (Current Problems of Psychiatry, 2011)
Aim: The purpose of this paper was to conduct a literature review on postpartum psychosis focusing upon the evaluation of its risk factors and prognosis.Method: A literature search was conducted in Medline for studies published between 1990 and 2011, using the key words: ‘postpartum psychosis’, ‘risk factors’, and ‘prognosis’.Conclusions:1. Postpartum psychosis severely disturbs the mother-child/infant relationship, posing a serious diagnostic and therapeutic challenge. 2. Risk factors for postpartum psychosis are most accurately reflected in the biopsychosocial model. 3. With a complete remission of symptoms and a well-preserved social and occupational functioning, the prognosis for PP is generally favorable in spite of a high rate of puerperal and nonpuerperal relapses and an increased frequency of suicide. 4. There is a need for preventive programmes providing multi-speciality care for women at high risk of PP throughout pregnancy and during the postpartum period.